2012
DOI: 10.1007/s00381-012-1786-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of pediatric high-grade gliomas with temozolomide treatment: a retrospective, multicenter study

Abstract: Initial or recurrent TMZ treatment in pediatric HGGs was safe and tolerable. Initial treatment showed improved PFS compared to recurrent treatment, and both showed similar OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There was a slightly better result in those patients receiving temozolomide in conjunction with radiotherapy, but this finding could not be confirmed on multivariate analysis. There are also some clinical trials emphasizing minimal or no benefit of temozolomide over conventional treatment in the pediatric group (10,22,25). Based on these, in this age group, a patient specific-discretion is warranted in balancing the risk of tumor growth with the benefits and complications of radiotherapy.…”
Section: █ Discussionmentioning
confidence: 99%
“…There was a slightly better result in those patients receiving temozolomide in conjunction with radiotherapy, but this finding could not be confirmed on multivariate analysis. There are also some clinical trials emphasizing minimal or no benefit of temozolomide over conventional treatment in the pediatric group (10,22,25). Based on these, in this age group, a patient specific-discretion is warranted in balancing the risk of tumor growth with the benefits and complications of radiotherapy.…”
Section: █ Discussionmentioning
confidence: 99%
“…We found that postoperative CCRT is an effective way to prolong the survival time and delay the recurrence for psGBM patients. Although current studies have found many differences between childhood and adult GBM, but the effect of the same treatment in adults and children is not consistent, however, many new treatment options are still in active investigation [3,11,14]. Nowadays, electric eld therapy is being hotly debated, it is an emerging treatment that can extend the life span of several months, it is also noninvasive and has little effect on children's growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…However, this correlation has not been replicated in paediatric HGG 1. Temozolomide has been used in children with estimated response rates of 12%–20%4 but with increased side effects, thrombocytopaenia being the most common. Retrospective analyses of temozolomide in paediatric HGG have not shown definite benefit, although randomised trials are lacking 2 4…”
Section: Discussionmentioning
confidence: 99%